2015
DOI: 10.3390/nano5031223
|View full text |Cite
|
Sign up to set email alerts
|

Modeling In Vivo Interactions of Engineered Nanoparticles in the Pulmonary Alveolar Lining Fluid

Abstract: Increasing use of engineered nanomaterials (ENMs) in consumer products may result in widespread human inhalation exposures. Due to their high surface area per unit mass, inhaled ENMs interact with multiple components of the pulmonary system, and these interactions affect their ultimate fate in the body. Modeling of ENM transport and clearance in vivo has traditionally treated tissues as well-mixed compartments, without consideration of nanoscale interaction and transformation mechanisms. ENM agglomeration, dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…Neither the ISDD nor ADSRM models consider the interaction of MNs with molecules present in the test system media. To overcome this limitation in the ASDRM model, the authors [54] extended the ADSRM model to consider the interaction of MNs with various fractions of lipids and surfactant proteins in the model. Another enhancement worth mentioning is the semi-analytical solution for the ISDD model developed by Mahnama et al [55] .…”
Section: Results On Available Pb Models Applicable To Mnsmentioning
confidence: 99%
See 2 more Smart Citations
“…Neither the ISDD nor ADSRM models consider the interaction of MNs with molecules present in the test system media. To overcome this limitation in the ASDRM model, the authors [54] extended the ADSRM model to consider the interaction of MNs with various fractions of lipids and surfactant proteins in the model. Another enhancement worth mentioning is the semi-analytical solution for the ISDD model developed by Mahnama et al [55] .…”
Section: Results On Available Pb Models Applicable To Mnsmentioning
confidence: 99%
“…However, the model can predict the dissolution of silver MNs. In a further publication, the same authors added the assessment of MN interaction with various fractions of lipids and surfactant proteins of the alveolar lining fluid, and applied the model also to 20–110 nm gold MNs and 600 nm SiO 2 particles [54] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Model predictions for agglomeration and dissolution were compared to in vitro measurements for various MNMs, coating materials, and incubation media, and found to be consistent with the measurements. The fate, transport, and effects of MNMs throughout the lung were also modelled to predict particle transport across the air/biological fluid interface and the final expected dose for both coated and uncoated particles[73] [74].…”
Section: Resultsmentioning
confidence: 99%
“…As airborne NPs are mainly absorbed by respiratory routes, some of the toxic effects of NPs on lungs have been described in both humans and experimental animals, being characterized mostly by inducible inflammatory reactions [ 144 ]. Still, inhaled NPs have a very small size and can be arrested from alveoli into other tissues by the bloodstream, which may lead to systemic harmful effects [ 148 ]. Indeed, it has been demonstrated that pulmonary instillation of titanium dioxide (TiO2) NPs has resulted in increased plaque deposits in atherosclerosis-prone apolipoprotein E-deficient mice [ 149 ].…”
Section: Cellular and Molecular Mechanisms Of Toxicity On Hematopomentioning
confidence: 99%